Luminescent MOFs for selective sensing of Ag+ and other ions (Fe(iii) and Cr(vi)) in aqueous solution. Issue 13 (15th March 2022) - Shao, Juan-Juan; Ni, Jian-Ling; Liang, Yu; Li, Guang-Jun; Chen, Li-Zhuang; Wang, Fang-Ming
Abstract : Two metal–organic frameworks, [Zn(BTA)2 ] n (LMOF- 1 ), [Zn3 (BTA)2 (5-tbuip)2 ] n (LMOF- 2 ) (BTA = 1 H -benzotriazole, 5-tbuip = 5- tert -butylisophthalic acid) have been solvothermally synthesized. They show strong blue luminescence and LMOF- 1 shows unusually detecting behavior to Ag + . Abstract : Two new title MOFs, [Zn(BTA)2 ] n (LMOF-1 ) and [Zn3 (BTA)2 (5-tbuip)2 ] n (LMOF-2 ) (BTA = 1 H -benzotriazole, 5-tbuip = 5- tert -butylisophthalic acid), have been synthesized by a solvothermal method. The structures of the two complexes have been determined by single-crystal X-ray diffraction analysis and further characterized by elemental analysis, IR spectroscopy, powder X-ray diffraction (PXRD) and thermogravimetric (TG) analysis. And the calculation of PLATON displays that the porosity values are 15.04% and 18.77%. Fluorescence analysis reveals that the two MOFs generate strong blue luminescence; LMOF-1 and LMOF-2 can be regarded as multiresponsive fluorescence sensors for Fe(iii ) and Cr(vi ) (CrO4 2− /Cr2 O7 2− ions) detection with high sensitivity and selectivity and a low detection limit in water via fluorescence quenching. It is worth noting that most LMOFs for detecting Ag + to date are mainly formed with rare earth lanthanide metals, while there are still few Zn-based LMOF probes used in Ag + detection. LMOF-1 can detect trace Ag + in water with a low detection limit. In addition, LMOF-1 has excellent water stability and thermal stability, and is an excellent material for detecting Ag + in daily water samples.